Aspects of rice culture (Oryza sativa L.) from high lands to zinc growing doses - Riva, D. C.; Santos, O.; Silva, R. M; Castro, Y. O. (Scientific Electronic Archives, 2019)
California farm 12 km from the headquarters of the municipality of Confresa-MT. Latitude 10Â° 38 ’38 "S and Longitude-55Â° 34’ 08" W, altitude of 200. The experiment was in DBC "A randomized block design, containing 5 treatments with 5 replicates. The treatments were composed of 5 doses of zinc and the doses: 0, 2, 4, 6 and 8 kg ha-1 of zinc using the zinc sulfate source. Characteristics evaluated were: Plant height, number of tillers and Productivity, with the exception of productivity, the other evaluations were made 75 days after sowing and when the crop reached physiological maturity the productivity was adjusted by adjusting the humidity to 13%. The treatment that most responded in the characteristic height of plant was the maximum dose 8 kg/ha-1 of zinc, being in average to the plants 97,04 cm. Both productivity and number of tillers followed the same trend with the best response at the dose of 2 kg ha-1 of zinc, with a mean of 6.21 tillers per plant, and yield of 2,685 kg ha-1. This means that the nutrient is used by the plant in a small quantity, even though it is very important for the metabolism of the plant.